Pemahaman Siswa Mengenai Kesehatan Reproduksi Remaja Melalui Layanan Informasi - Vicky Febry Wulandari; Herman Nirwana; . Nurfarhanah (Universitas Negeri Padang, 2012)
A student's understanding of reproductive health is very important. Not only the responsibility of the BKKBN, but there is a role that serves guidance and counseling to provide general information services to student's that aim's to equip student's with regard to the personal development of student's themselves, especially the physical development that occurs when reproductive organs are functioning. Research purpose to (1) describe the male and female student's understanding of adolescent reproductive health (2) test the understanding of the differences between male student's and adolescent girl's on reproductive health. Research methods used are descriptive comparative quantitative. This is a descriptive study with junior high school student's population in SMA Negeri 1 Padang by the number of 705 student's at year 2011/2012. Study sample numbered 173 people, chosen by using Multistage Random Sampling. Data were collected by questionnaire and processed with the technique mean, standard deviation, and T-Test. The result's revealed that student's understanding of reproductive health of adolescent's classified as medium, either male or female student's. There is no significant difference between the understanding of male or female student's.